Farmers’ knowledge, perception and management practices of fall armyworm (Spodoptera frugiperda Smith) in Manica province, Mozambique - Caniço, Albasini (2022)
This study aimed to gather information about farmers’ knowledge, perception and management practices of the newly introduced insect pest, the fall armyworm Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Manica province, Mozambique. A total of 200 smallholder farmers with experience in maize cultivation were surveyed using a semi-structured questionnaire. The survey was conducted between May and August 2019 in four districts: Macate, Manica, Sussundenga and Vanduzi. Most farmers were unable to morphologically identify fall armyworm (FAW) (from 93.9% in Vanduzi to 98.0% in Manica). Most farmers have experienced FAW damage in their farms (from 92% in Macate to 98.0% in Manica). Maize is mostly planted in October and November (from 44.0% in Sussundenga to 60.0% of farmers in Manica), but the highest infestation period is believed to be between November and February. With the exception of Vanduzi where 65.3% of farmers apply insecticides, most farmers in other districts do not use any method to control FAW (from 60.8% in Macate to 88.0% in Manica and Sussundenga respectively). Among those applying insecticides, from 65.0% in Manica to 75.0% in Vanduzi have confidence in the efficiency of the insecticides being used against FAW. Most farmers reported an increase in the spread of FAW. The lack of financial resources is reported as the main constraint in the fight against FAW. This study is the first of its nature in the province of Manica and provides valuable information that may support extension services and researchers when designing FAW management options for local smallholder farmers